The association between glycated hemoglobin, physical activity and infertility: a multiple logistic regression and mediation analysis based on the NHANES database - Chen, Panpan; Zhu, Leilei; Mou, Yanli; Zhao, Shuyun; Huang, Guanyou (Frontiers in Endocrinology, 2025)
ObjectiveTo determine the relationship between physical activity (PA) patterns and infertility among women in the United States and to ascertain whether glycated hemoglobin (HbA1c) influences this association.DesignA cross-sectional study of PA patterns and infertility was conducted. The PA classification was based on two categories: recreational PA and work-related PA. The subgroups were classified as inactive, less active, or active. We conducted data analysis via both multiple logistic regression analysis and mediation analysis.SettingNational Health and Nutrition Examination Survey (NHANES, 2013–2018).ParticipantsWomen aged 18–49 years (n, 3,948).ResultsThere was no statistically significant link demonstrated between infertility and work-related PA patterns. The recreational PA group may decrease the prevalence of infertility, with its occurrence being merely 0.79 times that of inactive group. (95% CI: 0.62, 1.0; p = 0.045). The consistency of this discrepancy was not preserved in Model III after the mixed effect was incorporated into the recreational PA group. The stratified research findings revealed that the association between recreational PA patterns and infertility was influenced by variables such as age, BMI, and history of diabetes. Furthermore, the mediation analysis revealed that recreational PA did not have a statistically significant direct effect on infertility (p = 0.098). HbA1c serves as a mediator in this interaction (95% CI: -0.06, -0.02).ConclusionRecreational PA patterns were associated with infertility among women aged 18–49 years in the United States, which was likely due to the effects of HbA1c.